METODE PEMBELAJARAN BERMAIN PERAN BERBASIS KONSEP TAT TWAM ASI UNTUK MENINGKATKAN EMPATI SOSIAL DAN HASIL BELAJAR SISWA KELAS V SD - Yuli Cahya Pratiwi, Ida Ayu; Gading, I Ketut; Edi Yudiana, I Kadek (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social empathy is the ability to understand and feel the conditions of others, which plays an important role in supporting the learning process, especially in characterbased subjects such as Pancasila Education. However, students’ social empathy in the field is still relatively low, in line with their low learning outcomes. Therefore, this study aims to examine the effect of a role-playing method based on the Tat Twam Asi concept on students’ social empathy and learning outcomes. This study employed a quantitative approach using a quasi-experimental method (pretestposttest control group design) involving 41 fifth-grade students of SDN Gugus I Karangasem as the research subjects. Data were collected through questionnaires and learning outcomes tests and analyzed using MANOVA. The results showed a significant simultaneous effect (p < 0.05), with social empathy increasing from 40.82 to 61.68 and learning outcomes from 49.09 to 82.05. Thus, the method is effective in improving students’ social empathy and learning outcomes.